Macroeconomic effects of the geography of knowledge production: EcoRET, a macroeconometric model with regionally endogenized technological change for Hungary - Hans Joachim Schalk; Attila Varga (European Regional Science Association (ERSA), 2004)
Mainstream economic thinking is still characterized by a predominantly a-spatial theoretical structure. Though economists are able to model the impacts of capital, labor or technology on output, employment or prices at both macro and micro levels, our methodological tools are still not sensitive to the influence of geography on the way inputs contribute to production. Empirical investigations of the relationship between agglomeration and macroeconomic growth are still relatively rare in the literature. It is also a very recent advancement that geographical structure is modeled simultaneously with other variables in macroeconomic models. This paper introduces EcoRET the macroeconometric model with regionally endogenized technological change for Hungary. The unique feature of EcoRET is that it incorporates spatial structure into a traditional macroeconometric model by a regional block of technological change. The model can be applied for policy simulations on the macroeconomic effects of changing geographical distribution of regional financial supports. JEL classification: O31, H41, O40 Keywords: endogenous growth theory, new economic geography, knowledge spillovers, total factor productivity, agglomeration economies
Keywords: O31; H41; O40; 330; endogenous growth theory; new economic geography; knowledge spillovers; total factor productivity; agglomeration economies